Oil and gas perspectives of pliocene-miocene in South-East of Absheron Peninsula based on latest 3D data - Ahmadov, T.R. (Revista de la Universidad del Zulia, 2019)
The paper is devoted to hydrocarbon perspectives in Pliocene and Miocene in south-east of Absheron peninsula based on 3D seismic data. Paper starts with brief description of history of commercial hydrocarbon production across the peninsula, the oldest oil-gas region of the world. It is noted that major production targets here are within Productive Series (PS) of Lower Pliocene. Oil and gas perspectives of this part of Absheron peninsula is related to PS and underlying deposits, studied in general by seismic survey. Kala suite of PS includes all major hydrocarbon horizons exploited currently. The general scheme of Kala suite layers is given in the paper. According to cyclo-stratigraphic model of Kala layers designed by data from several wells a large number of unconformity surfaces have been outlined evidencing unstable paleogeography and paleomorthology of sedimentation. Due to the absence of Paleogene-Miocene deposits available for studies in recovered part of section, we have used similar fields and regional paleogeographic maps for this region. Data analysis made it possible to derive that most favorable conditions for hydrocarbon accumulations in Paleogene-Miocene reservoirs is on Absheron peninsula. In Miocene the unrecovered oil resources is attributed majorly to reservoirs of Diatom suite and Chokrak horizon. The expected deposit types are lithological-stratigraphic and tectonically sealed. It must be noted that one of major tectonic factors of realization of oil and gas resources and hydrocarbon migration is presence of faults sufficiently outlined by 3D seismic data. The paper also considers major risks of exploration for traps in Paleogene-Neogene.